The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1126/scirobotics.aaz6451
|View full text |Cite
|
Sign up to set email alerts
|

An autonomous untethered fast soft robotic insect driven by low-voltage dielectric elastomer actuators

Abstract: Insects are a constant source of inspiration for roboticists. Their compliant bodies allow them to squeeze through small openings and be highly resilient to impacts. However, making subgram autonomous soft robots untethered and capable of responding intelligently to the environment is a long-standing challenge. One obstacle is the low power density of soft actuators, leading to small robots unable to carry their sense and control electronics and a power supply. Dielectric elastomer actuators (DEAs), a class of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
302
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 354 publications
(324 citation statements)
references
References 50 publications
2
302
0
Order By: Relevance
“…Their size and shape could be adapted to each body part to provide an electrically controlled, lightweight, full‐body haptic suit. By reducing film thicknesses and using different materials, we plan to reduce the drive voltage to below 500 V, a value below which compact electronics are much easier to manufacture; for example, Ji et al [ 44 ] reported 350 mg two‐channel 500 V circuits for untethered mobile robots.…”
Section: Figurementioning
confidence: 99%
“…Their size and shape could be adapted to each body part to provide an electrically controlled, lightweight, full‐body haptic suit. By reducing film thicknesses and using different materials, we plan to reduce the drive voltage to below 500 V, a value below which compact electronics are much easier to manufacture; for example, Ji et al [ 44 ] reported 350 mg two‐channel 500 V circuits for untethered mobile robots.…”
Section: Figurementioning
confidence: 99%
“…Another significant concern is that the requirement for high voltage could hinder the proposed actuator for practical applications. It is noticed that, recently, Ji et al have largely addressed this issue by fabricating stacked ultrathin DE membranes, powered by a low voltage of 450 V [46]. They clarified that below 500 V, there exists a vast selection of low-mass, miniature, commodity surface-mount components, enabling complex kilohertz voltage sources weighing only tens or hundreds of milligrams to be integrated into soft robotic systems.…”
Section: Discussionmentioning
confidence: 99%
“…These electrodes add nearly negligible stiffness to the elastomer, and have a low enough resistance to allow operation at several hundred Hz. [46] Two versions of FT haptic devices are presented here ( Figure 1). The first version uses a flexible frame (Figure 1a,b) to maintain the DEA pre-stretch and to facilitate the electrical connection between the DEA electrodes and very thin wires.…”
Section: Operating Principle Of the "Feel-through" Haptic Devicementioning
confidence: 99%